Nitrogen-doped biomass activated carbon induced uniform lithium deposition for highly stable lithium metal anodes. (March 2023) - Yu, Juan; Peng, Jiaxin; Meng, Bicheng; Wang, Xuyang; Wang, Tian; Jia, Xuefeng; Yang, Kai; Yang, Naixing; Li, Linbo
Abstract: Uncontrollable lithium dendrite growth hinders lithium metal anode commercial application. Therefore, a copper current collector modified by nitrogen-doped biomass activated carbon (PAC@Cu) was designed to induce the uniform deposition of lithium ions. The abundant pore structure of activated carbon can limit the disordered growth of lithium dendrites, and the abundant nitrogen-containing functional groups provide a large number lithiophilic sites. The symmetrical cells of PAC-1@Cu exhibited up to 220 h of cycle life at 1 mA cm −2 and 1 mAh cm −2 . The results provide guidance for the practical application and design of high-performance and low-cost lithium metal batteries. Highlights: Nitrogen-doped persimmon biomass activated carbon (PAC) modify commercial Cu foils. Nitrogen-containing functional groups induced uniform nucleation and deposition of lithium. Hierarchical porous structure and high specific surface area of PAC suppress the growth of lithium dendrites.